Immune Response to Dengue Fever Infection in Endemic Areas of Lombok Barat - Erlin Yustin Tatontos; Ersandhi Reshnleksmana; Urip (Postgraduate, University of Mataram, 2025)
Dengue infection makes the body create immune responses, such as the formation of immunoglobulins. In Lombok Barat, 222 DHF cases with three fatalities are reported, with a CFR of 1.4%. The aim of this study was to determine the immune response to dengue fever in West Lombok. Analytical observational research method with cross-sectional study. Population included DHF patients in endemic areas of Lombok Barat, a total of 33 respondents suspected of dengue fever. Data on immune responses were gathered using dengue IgM and IgG tests. Respondent immune responses exhibited that 21.2% tested positive and 78.8% tested negative for IgM, while 63.6% tested positive and 36.4% tested negative for IgG. Statistical analysis of dengue fever infection with IgM using the Chi-square test obtained p = 0.049 <α = 0.05, while dengue fever infection with IgG was p = 0.113 > α = 0.05. The results of the analysis showed that there was a significant relationship between dengue fever infection and IgM test results, but there was no significant relationship between dengue fever infection and IgG test results. Most of the DHF infections in Lombok Barat were categorized as primary infections.